Intensity and Prevalence of Ectoparasites in Tilapia (Oreochromis niloticus) Seeds at the Tlogowaru Fish Seed Center, Malang City - Andini, Saskia Ade Hutami Fery; Sjakoer, Nour Athiroh Abdoes; Latuconsina, Husain (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
One of the problems in the fish farming sector is the outbreak of infectious diseases caused by parasites. The presence of parasites can cause poor quality and affect the growth and reproduction of fish. This study aims to identify the types of ectoparasites, intensity and prevalence of ectoparasites that infect tilapia (Oreochromis niloticus). The research was carried out in February - March 2021 at the Tlogowaru Fish Seed Center, Malang City. Determination of the pond as a sampling location purposively based on the length of the fish fry. Pool A contains fish seeds measuring 7-9 cm, pool B contains fish seeds measuring 9-11 cm, and pool E, tilapia measuring 12-15 cm. A total of 36 fish samples were taken at random, from each pond 12 samples were taken using the simple random sampling method. Found as many as 3 types of ectoparasites that infect tilapia fry (Oreochromis niloticus), namely: Trichodina sp., Gyrodactylus sp., and Epistylis sp. The highest prevalence value was found in the parasite Trichodina sp. by 75% and the lowest prevalence value in the parasite Gyrodactylus sp. by 16.6%. The highest intensity value was obtained from the ectoparasite Trichodina sp. of 3.33 ind/head and the lowest intensity value was on the parasite Gyrodactylus sp. of 0.57 ind/head. The type of ectoparasite that was found to be the most dominant in infecting value fish was Trichodina sp. The quality of pond water, especially fluctuating temperature and pH, is thought to be the influence of infection in tilapia (Oreochromis niloticus).